2019
DOI: 10.1371/journal.pone.0210434
|View full text |Cite
|
Sign up to set email alerts
|

Recent incidence and surgery trends for prostate cancer: Towards an attenuation of overdiagnosis and overtreatment?

Abstract: BackgroundScreening for prostate cancer is frequent in high-income countries, including Switzerland. Notably due to overdiagnosis and overtreatment, various organisations have recently recommended against routine screening, potentially having an impact on incidence, mortality, and surgery rates. Our aim was therefore to examine whether secular trends in the incidence and mortality of prostate cancer, and in prostatectomy rates, have recently changed in Switzerland.MethodsWe conducted a population-based trend s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Overall, more than 50% of patients with first prostate cancer are treated with surgery including radical prostatectomy [41]. In Switzerland, prostate cancer incidence rates have recently decreased after a sustained increase up to 2002, most likely due to changes in screening and work-up practices [42]. Higher socioeconomic position (SEP) has been shown to be associated with more frequent prostate-specific antigen (PSA) screening, earlier diagnosis [28,43] and higher prostate cancer incidence compared to men with lower SEP. [44,45] In addition, men of higher SEP are generally more health conscious than the general male population [46] and thus less likely to O: number of observed cases E: number of expected cases SIR: standardized incidence ratio 95%CI: 95% confidence intervals be exposed to cancer risk such as cigarette smoking and alcohol consumption.…”
Section: Discussion In the Context Of The Literaturementioning
confidence: 99%
“…Overall, more than 50% of patients with first prostate cancer are treated with surgery including radical prostatectomy [41]. In Switzerland, prostate cancer incidence rates have recently decreased after a sustained increase up to 2002, most likely due to changes in screening and work-up practices [42]. Higher socioeconomic position (SEP) has been shown to be associated with more frequent prostate-specific antigen (PSA) screening, earlier diagnosis [28,43] and higher prostate cancer incidence compared to men with lower SEP. [44,45] In addition, men of higher SEP are generally more health conscious than the general male population [46] and thus less likely to O: number of observed cases E: number of expected cases SIR: standardized incidence ratio 95%CI: 95% confidence intervals be exposed to cancer risk such as cigarette smoking and alcohol consumption.…”
Section: Discussion In the Context Of The Literaturementioning
confidence: 99%
“…Furthermore, neither involved participants from the United Kingdom (UK), thereby limiting the generalisability of findings to this patient population and the National Health Service. This is of particular importance as, owing to differences in screening practices across Europe and North America, a relatively high proportion of patients present with advanced disease at the time of diagnoses in the UK [14–18].…”
Section: Introductionmentioning
confidence: 99%
“…Risk stratification is critical for PCa patients, both following a new diagnosis and after radical treatment. Although AS application is expanding, the overtreatment of PCa remains a concern in these patients 23,24 . In addition, it was reported that approximately 24%–34% of men with BCR are expected to progress to clinically evident recurrence within 15 years after RP.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the same histological and clinical parameters might show significantly different molecular characteristics and have different clinical predictions 27 . Although the risk stratification of PCa, developed by D'Amico, 28 has been adopted by the National Comprehensive Cancer Network and is widely used in related treatment decision‐making, overdiagnosis and over or undertreatment remain important concerns among PCa patients 24,29 . Thus, uncovering more powerful methods to identify PCa patients who are at a higher risk of progression seems crucial.…”
Section: Discussionmentioning
confidence: 99%